α-Mangostin improves glucose uptake and inhibits adipocytes differentiation in 3T3-L1 cells - Mohamed Amiroudine, Mohamed Zaffar Ali; Bakhtiar, M. Taher; Darnis, Deny Susanti; Arief Ichwan, Solachuddin Jauhari; Kaderi, Mohd Arifin; Zakaria, Zainul Amiruddin (2014)
α-Mangostin is a major compound found in mangosteen fruit hull and it has been reported to have wide range of pharmacological activities. The current study seeks to evaluate the in vitro activities of α-mangostin on adipocyte differentiation, glucose uptake and related gene expressions. The inhibitory effect of the compound on lipid accumulation of 3T3-L1 preadipocytes was determined by Oil Red O staining method. Glucose uptake and free fatty acid release from the medium were determined by using 2-deoxy-D-[3H] glucose and adipolysis kit, respectively. Finally, the evaluation of related gene expression was carried out by the quantitative reverse transcriptase polymerase chain reaction (gRT-PCR). Depending on the dose, cell treated with α-mangostin was found to inhibit the cytoplasmic lipid accumulation as well as adipogenic differentiation of preadipocyte. Analyses of 2-deoxy-D-[3H] glucose uptake activity showed that α-mangostin significantly improved the glucose uptake (p<0.05). In addition, α-mangostin increased the amount of free fatty acid released. qRT-PCR analysis showed that the α-mangostin reduced lipid accumulation by inhibition of PPARγ gene expression. The induction of glucose uptake and free fatty acid release by α-mangostin were accompanied by increasing mRNA expression of GLUT4 and leptin. In summary, these evidences proposed that α-mangostin might be beneficial for obesity management.